An examination of the prevalence and characteristics of UK community males who hold a sexual interest in children using the revised interest in child molestation scale. Issue 10 (26th November 2021) - O'Connor, Alisha; Gannon, Theresa A.
ABSTRACT: Research suggests that a significant proportion of community males hold a sexual interest in children. However, sexual interest in children is not synonymous with offending. We explore rates of community male interest in child sexual abuse (CSA) using the Interest in Child Molestation Scale-Revised (ICMS-R). We also examine the ICMS-R's susceptibility to socially desirable responding and assess how interest in CSA relates to sexual interest in pre-pubescent children. Results indicate that up to 40% of participants reported some interest in CSA. Findings suggest that the ICMS-R does not appear to be influenced by socially desirable responding, and that sexual interest in pre-pubescent children is a significant predictor of ICMS-R scores. In study two, we explore the characteristics associated with a sexual interest in children and behavioral proclivity to offend. Men reporting at least some sexual arousal to ICMS-R scenarios had greater endorsement of beliefs supporting CSA and experienced more fantasies and/or behaviors involving CSA than men reporting no arousal. Participants reporting arousal alongside behavioral proclivity to offend held more CSA supportive beliefs, were more likely to use sex as a coping strategy, and experienced more fantasies and/or behaviors involving CSA than those reporting arousal with no behavioral proclivity to offend.